Tension pneumoperitoneum - Mérola, L (Cirugía del Uruguay, 2020)
An observation of tension pneumoperitoneum is presented, due to a perforated ulcus, which had to be punctured before the surgical intervention. The severe symptoms of respiratory failure, which made active treatment impossible, were thus improved.